2020
DOI: 10.1021/acs.analchem.9b05390
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probe for Transmembrane Dynamics during Osmotic Effects

Abstract: Membrane tension pores determine organelle dynamics and functions, giving rise to physical observables during the cell death process. While fluorescent organelle-targeted probes for specific chemical analytes are increasingly available, subcellular dynamic processes involving not only chemical parameters but also physicochemical and physical parameters are uncommon. Here, we report a mitochondrial chemical probe, named RCN, rationally designed to monitor osmotic effects during transmembrane tension pore format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…It is also in line with a recent report on a solvatochromic mitochondria-specific probe. 54 The peculiar behavior of lysosomes (e.g. lower polarity and higher LOP) is probably because they are expected to shrink, which induces higher lipid ordering at the inner leaflet of the vesicles, where NRLyso locates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also in line with a recent report on a solvatochromic mitochondria-specific probe. 54 The peculiar behavior of lysosomes (e.g. lower polarity and higher LOP) is probably because they are expected to shrink, which induces higher lipid ordering at the inner leaflet of the vesicles, where NRLyso locates.…”
Section: Resultsmentioning
confidence: 99%
“…34,[45][46]49 It revealed that the intracellular biomembranes are significantly more polar (less ordered) than plasma membranes. 46 Second approach exploited specific targeting of solvatochromic dyes to organelle of interest, 5,25,[35][36][50][51][52][53] including mitochondria 32,50,54 and ER. 35 However, these studies were focused on targeting one particular organelle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that BODIPY‐Ref also exhibited interesting membrane permeability with a non‐specific localization in the perinuclear zone. Further, this fluorophore was able to specifically localize apoptotic vesicles and cellular blebs during cell oxidative stress [25] . The low‐dose stimulus with H 2 O 2 was used in order for the blebs to be well‐contrasted under the green channel illumination, allowing a bright in‐plane bleb visualization with clean green‐emission on these membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Further, this fluorophore was able to specifically localize apoptotic vesicles and cellular blebs during cell oxidative stress. [25] The low-doses timulus with H 2 O 2 wasu sed in order for the blebst ob ew ell-contrasted under the green channel illumination, allowing ab right in-plane bleb visualization with cleangreen-emission on these membranes. At this point, we were motivated to investigate the origin of the divergentc ell uptake efficiency and subcellular localization of these molecules, with the most striking differencesa rising from BODIPY-o-Ph-CB and BODIPY-m-Ph-CB.…”
Section: Cellular Uptake and Intracellular Localizationmentioning
confidence: 99%